Hypomagnetic Field and Its Effect on the Growth and Survival of Microorganisms - Sincak, Miroslava; Benediktová, Kateřina; Adámková, Jana; Sedlakova-Kadukova, Jana (Microorganisms, 2025)
As humanity embarks on interplanetary exploration and envisions future colonies beyond Earth, understanding the impact of extreme environments on life becomes paramount. Among these factors, the hypomagnetic field (HMF)-a condition where the protective geomagnetic field is absent-remains poorly understood, especially regarding its effects on (micro)organisms. To our knowledge, this is the first study to examine how short-term exposure to an HMF (24 h to 7 days) affects the growth of three different microorganisms, Saccharomyces cerevisiae, Acidithiobacillus ferrooxidans, and Lactobacillus plantarum, using a specialized hypomagnetic chamber and advanced spectrophotometric analysis. We demonstrate significant growth inhibition in S. cerevisiae (23%) and A. ferrooxidans (68%), with L. plantarum remaining unaffected. This inhibitory effect appears reversible, diminishing as organisms return to normal geomagnetic conditions. These findings reveal that the HMF acts as a temporary environmental stressor, underscoring the need for deeper exploration of its biological effects. Our work sets the stage for further research into how the space environment may shape microbial ecosystems critical to future human endeavors in space.
Keywords: hypomagnetic field; yeast; bacteria; microorganisms; growth inhibition; environmental stress